A ocorrência de anticorpos anti-Leptospira em cães na região sudeste do estado de São Paulo - Gomes, N.; Souza-Filho, A. F.; Gonçales, A. P.; Pinto, C. M.; Onofrio, V. C.; Souza, G. O.; Guedes, I. B.; Abreu, J. A. P.; Cortez, A.; Heinemann, M. B. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an emerging disease with different prevalence in dogs’ populations. Dogs play an important role in the disease epidemiology, acting as accidental or maintenance hosts. Infective serovars present different geographic distribution among these populations, depending on exposure to hosts from infected wild or domestic animal reservoirs. The most common serovars that infect dogs, prior to the introduction of the vaccines against leptospirosis, were Icterohaemorrhagiae and Canicola.